No-where but here - McGarry, Katie (McGarry, Katie. Thunder Road series., 2015)
When a reluctant visit turns into an extended summer vacation among relatives Emily never knew she had, one thing becomes clear: nothing is what it seems. Not the club, not her secret-keeping father and not Oz, a guy with suck-me-in blue eyes who can help her understand them both.